2013
DOI: 10.2337/dc12-0320
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Reactivity of Skin Microcirculation in Response to l-Arginine in Later-Onset Type 1 Diabetes

Abstract: OBJECTIVEThe aim of our study was to evaluate the vasodilatory effect of l-arginine infusion on the skin microcirculation and to assess the relationship between this effect and the presence of microangiopathy in patients with type 1 diabetes.RESEARCH DESIGN AND METHODSCapillaroscopy was performed before and after l-arginine infusion in 48 diabetic patients (26 women and 22 men; age, 39.8 ± 6.3 years) and 24 volunteers free of any chronic disease (13 women and 11 men; age, 38.0 ± 6.7 years). The skin microcircu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 27 publications
2
38
0
1
Order By: Relevance
“…Skin microvascular function measurements are easy, non‐invasive, and fast and are considered a representative model for generalized microvascular (dys)function, including microvascular (dys)function in the brain. Several studies have demonstrated abnormalities in peripheral and cerebral microvascular function in type 1 diabetes patients. In the present study, we were unable to detect significant differences in baseline skin microvascular function, yet baseline and peak hyperemia capillary density are lower in the type 1 diabetes patients, indicating a possible power problem.…”
Section: Discussionmentioning
confidence: 99%
“…Skin microvascular function measurements are easy, non‐invasive, and fast and are considered a representative model for generalized microvascular (dys)function, including microvascular (dys)function in the brain. Several studies have demonstrated abnormalities in peripheral and cerebral microvascular function in type 1 diabetes patients. In the present study, we were unable to detect significant differences in baseline skin microvascular function, yet baseline and peak hyperemia capillary density are lower in the type 1 diabetes patients, indicating a possible power problem.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the skeletal muscle microvascular responses to insulin were [50,51]. abnormal in late-stage diabetes and in obesity The use of LDF in T1DM patients belonging to a wide age-range (children, adolescents, and young adults) has shown decrased endothelium-dependent and independent vasodilation possibly due to poor glycemic control and T1DM duration [42,[52][53][54][55]. Moreover, a recent study by Tibirica et al [56] in young T1DM patients without other chronic co-morbidities, assessed by intravital video capillaroscopy, has shown significantly impaired skin capillary function in both fingers and toes.…”
Section: Diabetic-induced Changes In the Human Microcirculationmentioning
confidence: 99%
“…In hypertension there is reduced capillary density . One study demonstrated reduced microvascular reactivity in patients with later onset type 1 diabetes …”
Section: Circulationmentioning
confidence: 99%